Monetary policy and the asset risk-taking channel - Angela Abbate; Dominik Thaler (Deutsche Bundesbank, 2015)
Motivated by VAR evidence, we develop a monetary DSGE model where an agency problem between bank financiers, stemming from limited liability and unobservable risk taking, distorts banks' incentives leading them to choose excessively risky investments. A monetary policy expansion magnifies these distortions, increasing excessive risk taking and lowering the expected return on investment. We estimate the model on US data using Bayesian techniques and assess how this novel channel affects optimal monetary policy. Our results suggest that the monetary authority should stabilize the real interest rate, trading off more inflation volatility in exchange for less volatility in risk taking and output.
Keywords: E12; E44; E58; 330; Bank Risk; Monetary policy; DSGE Models